Design and Analysis of Equilateral Triangular Single Patch Antenna with Side Length 8cm - Ngu, Sze Song; Kho, Lee Chin; Bong, David B L; Shamsiah, Binti Suhaili (IEEE, 2007)
Nowadays, different types of antenna were designed by using different parameters. Researchers take into consideration different parameters such as radiation pattern, power handling capability, frequency range, bandwidth, power gain, polarization, beam width, coverage, input impedance and the others when designing an antenna. The antenna's practicability, efficiency and cost remain the most critical issues in antenna design. In this paper, the details regarding antenna design parameters and considerations are shown. The design of equilateral triangular single patch antenna with length 8cm and other suitable choices of thickness, material of patch and feeding technique is presented. Microwave Office software is used throughout the research for the simulation data modeling and analysis. The simulated resonant frequency is compared to the calculated resonant frequency.